Effects of timely case conferencing between general practitioners and specialist palliative care services on symptom burden in patients with advanced chronic disease: results of the cluster-randomised controlled KOPAL trial - Tina Mallon; Josefine Schulze; Nadine Pohontsch; Thomas Asendorf; Jan Weber; Silke Böttcher; Uta Sekanina; Franziska Schade; Nils Schneider; Judith Dams; Michael Freitag; Christiane Müller; et al. (BMC Palliative Care)
Abstract Background Patients with advanced chronic non-malignant conditions often experience significant symptom burden. Therefore, overcoming barriers to interprofessional collaboration between general practitioners (GPs) and specialist palliative home care (SPHC) teams is essential to facilitate the timely integration of palliative care elements. The KOPAL trial aimed to examine the impact of case conferences between GPs and SPHC teams on symptom burden and pain in patients with advanced chronic heart failure, chronic obstructive pulmonary disease, and dementia. Methods The cluster-randomised controlled trial compared a structured palliative care nurse visit followed by an interprofessional case conference to usual care. Data were collected from GPs at baseline and 48 weeks, while standardised patient interviews were conducted at baseline, 6, 12, 24, and 48 weeks. Results We analysed 172 patients from 49 German GP practices. Both groups showed marginal improvement in symptom burden; however, no statistically significant between-group difference was found ( $$\:{Δ\:}$$ =-0.561, 95% CI: -3.201–2.079, p = .68). Patients with dementia experienced a significant pain reduction ( $$\:{Δ\:}$$ =2.187, 95% CI: 0.563–3.812, p = .009). Conversely, the intervention did not have a significant effect on pain severity ( $$\:{Δ\:}$$ =-0.711, 95% CI: -1.430 − 0.008, p=.053) or pain interference ( $$\:{Δ\:}$$ =-0.036, 95% CI:-0.797 − 0.725, p=.926) in other patient groups. Conclusions The intervention showed promise in the timely introduction of palliative care elements to address pain management in patients with dementia. Further studies are needed to identify and effectively address symptom burden and pain in other patient groups. Trial registration German Clinical Trials Register: https://www.drks.de/DRKS00017795 (Registration date: 9th January 2020).